Rancang Bangun Sistem Informasi Pengolahan Data Penerimaan dan Pengeluaran Kas Pada Organisasi Pimpinan Cabang Muhammadiyah SU.I Palembang Berbasis Web - Martadinata, Fendri; Firdaus, Ahmad; Lonando, Paray Theo; Nursalam, M. Vikram (Jurnal Pengembangan Sistem Informasi dan Informatika, 2023)
Introduction: The Muhammadiyah SU.I Branch Leadership Organization is a structural level of Muhammadiyah at sub-district level in the Seberang Ulu I sub-district area. The Muhammadiyah Branch Leadership has a coordinating function for all Muhammadiyah Leadership in the sub-district area, as well as coordinating the Islamic da'wah movement throughout the sub-district area. through various forms, such as religious activities, education, social welfare, health, and so on. Management of cash receipts and disbursements data at the Muhammadiyah SU.I Branch Leadership Organization currently still uses spreadsheets. Disadvantages of using this spreadsheet include the possibility of high data redundancy, difficulty checking inputted data for errors, difficulty in searching for data and low file security. This causes the process of making reports by employees to be slow and the leadership not making decisions quickly. Purpose: The aim of the research is expected to make it easier for employees to manage data on cash receipts and disbursements quickly and accurately, so that it can help leaders in making decisions. Research Method: This research uses data collection techniques using qualitative methods. Namely by interviews and observations as well as a waterfall design. Results: The results of the research were to create a "Web-Based Design and Development of an Information System for Data Processing Cash Receipts and Disbursements at the Muhammadiyah SU.I Palembang Branch Leadership Organization". Conclusion: The conclusion of this research is that the Muhammadiyah SU.I Palembang Branch Leadership Organization needs an information system to manage web-based cash receipts and disbursements data quickly and precisely.